2021
DOI: 10.21203/rs.3.rs-392256/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of laboratory waste management and laboratory staff awareness in Khartoum state

Abstract: Background A good environmental health conditions is a challenge worldwide. However, Majority of Laboratory wastes extremely dangerous to the environment, animals, and human because of increasing numbers of laboratories and health facilities especially on big cities in Africa like Khartoum state Capital of Sudan. Materials and Methods A cross-sectional study was carried out on a group included 36 laboratories in Khartoum state from February to march 2021. Approvals have taken from each laboratory and participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In Sudan, several studies isolated Enterobacteriaceae; E. coli among other species were isolated by Hussein 6 from fresh meat samples; Abd ElRahman 7 isolated E. coli from 17% of minced meat samples; Mohamed 8 found that 6% of meat samples were E. coli beneficial; Ahmed 8 and Ahmed 9 identified E. coli in ready to eat beef burger in Khartoum State and found that the total coliform bacteria observed in 48.8% of samples and 9.3% of them were positive for E. coli. Warsama et al 11 isolated E. coli in 11.1% of food samples, and Salmonella Typhi in 11.1% of them.…”
Section: Introductionmentioning
confidence: 99%
“…In Sudan, several studies isolated Enterobacteriaceae; E. coli among other species were isolated by Hussein 6 from fresh meat samples; Abd ElRahman 7 isolated E. coli from 17% of minced meat samples; Mohamed 8 found that 6% of meat samples were E. coli beneficial; Ahmed 8 and Ahmed 9 identified E. coli in ready to eat beef burger in Khartoum State and found that the total coliform bacteria observed in 48.8% of samples and 9.3% of them were positive for E. coli. Warsama et al 11 isolated E. coli in 11.1% of food samples, and Salmonella Typhi in 11.1% of them.…”
Section: Introductionmentioning
confidence: 99%